Active sway control of a gantry crane by an electrical ducted fan - Maghsoudi, Mohammad Javad (International Institute of Acoustics and Vibrations, 2015)
Sway reduction is very vital in a nonlinear oscillatory system such as a gantry crane. In this paper, a new design is proposed for active sway control of a gantry crane using an electrical ducted fan. The thrust force developed by the motor is used to cancel out payload oscillation. A dynamic model of the crane with a ducted fan is derived and simulated using Matlab. Performance of the proposed technique is investigated for a crane subjected to initial sway and an external force input. In addition, cases with different payloads and cable lengths are also studied. Simulation results show satisfactory performance of the fan-controlled system in eliminating the payload sway. The proposed design can also handle changes in payload and cable length. A main advantage of this approach is that it does not require modeling of the crane in real time experiments.